Seroprevalence of Toxoplasma gondii in mithun (Bos frontalis) from north eastern hilly region of India - Chamuah, J. K. (J Parasit Dis, 2013)
Mithun (Bos frontalis) is mostly utilized for meat purpose by the local tribal people of north eastern hilly region of India. Meat born diseases are very important issues for the people of these areas from the public health point of view. In order to realize the issues, the serological prevalence of Toxoplasmosis was carried out as per ELISA kit (CHEKIT* TOXOTEST, IDEXX Laboratory, USA) to find out Toxoplasma gondii antibody. As a whole, out of 195 animals examined, only 8 (4.10 %) animals were found to be suspected and one (0.51 %) animal was  found to be positive in this precious animal of the north eastern region.